Proposta de um dispositivo visual para utilização de linha de vida horizontal - Grande, Fernando; Longo, Ramon; Lantelme, Elvira Maria Vieira; Costella, Marcelo Fabiano (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
One of the main protective equipment used to prevent falls is the lifeline. However, at the construction site, this equipment is deficient in visual identification, as there is a lack of information on how to use it properly. The purpose of the study is to create a visual device for guidance on the use of lifeline equipment in construction. As for the research method, a literature review was initially performed. In a second moment, a technical visit was made to a company. The last step consisted of data analysis and the proposition of the device model to orient activities that use lifelines following the model proposed by Valente (2017). The results show the development of a visual device in three parts: a description of the activity to be developed, the protection equipment used and information on how to react in case of an accident at work. The study highlights two contributions: the probable reduction in the number of accidents due to the misuse of lifeline equipment and the validation of the method proposed by Valente (2017) for the design of visual devices.One of the main protective equipment used to prevent falls is the lifeline. However, at the construction site, this equipment is deficient in visual identification, as there is a lack of information on how to use it properly. The purpose of the study is to create a visual device for guidance on the use of lifeline equipment in construction. As for the research method, a literature review was initially performed. In a second moment, a technical visit was made to a company. The last step consisted of data analysis and the proposition of the device model to orient activities that use lifelines following the model proposed by Valente (2017). The results show the development of a visual device in three parts: a description of the activity to be developed, the protection equipment used and information on how to react in case of an accident at work. The study highlights two contributions: the probable reduction in the number of accidents due to the misuse of lifeline equipment and the validation of the method proposed by Valente (2017) for the design of visual devices.